Advances of DNA Damage Repair-Related Drugs and Combination With Immunotherapy in Tumor Treatment - Wang, Yumin; Duan, Meihan; Peng, Zhouying; Fan, Ruohao; He, Yuxiang; Zhang, Hua; Xiong, Wei; Jiang, Weihong (Frontiers in Immunology, 2022)
Cancer therapy has been an important and popular area in cancer research. With medical technology developing, the appearance of various targeted drugs and immunotherapy offer more choices to cancer treatment. With the increase of drug use, people have found more and more cases in which tumors are resistant to DDR-based drugs. Recently, the concept of combination therapy has been brought up in cancer research. It takes advantages of combining two or more therapies with different mechanisms, aiming to benefit from the synergistic effects and finally rescue patients irresponsive to single therapies. Combination therapy has the potential to improve current treatment of refractory and drug-resistant tumors. Among the methods used in combination therapy, DNA damage repair (DDR) is one of the hottest. Recent researches have shown that combined application of DDR-related drugs and immunotherapies significantly improve the therapeutic outcomes of malignant tumors, especially solid tumors.